A study of TiB2/TiB gradient coating by laser cladding on titanium alloy. (July 2016) - Lin, Yinghua; Lei, Yongping; Li, Xueqiao; Zhi, Xiaohui; Fu, Hanguang
Abstract: TiB2 /TiB gradient coating has been fabricated by a laser cladding technique on the surface of a Ti–6Al–4V substrate using TiB2 powder as the cladding material. The microstructure and mechanical properties of the gradient coating were analyzed by SEM, EPMA, XRD, TEM and an instrument to measure hardness. With the increasing distance from the coating surface, the content of TiB2 particles gradually decreased, but the content of TiB short fibers gradually increased. Meanwhile, the micro-hardness and the elastic modulus of the TiB2 /TiB coating showed a gradient decreasing trend, but the fracture toughness showed a gradient increasing trend. The fracture toughness of the TiB2 /TiB coating between the center and the bottom was improved, primarily due to the debonding of TiB2 particles and the high fracture of TiB short fibers, and the fracture position of TiB short fiber can be moved to an adjacent position. However, the debonding of TiB2 particles was difficult to achieve at the surface of the TiB2 /TiB coating. Highlights: The gradient distribution of TiB2 /TiB was caused by the substrate dilution and in situ reaction. The gradient distribution of TiB2 /TiB can affect the gradient variation of the micro-hardness and elastics modulus. TiB2 particle fracture mode and TiB fiber orientation can affect the variation of the fracture toughness.